Análisis de procesos licitatorios y asignación de riesgos en asociaciones público privadas (caso: ruta del cacao, colombia) (2020)
For Colombia and for all the countries of the world, the developing of infrastructure has been an important factor in increasing the economy since it allows reducing the social gap and increasing competitiveness since it facilitates the transport of people, goods, merchandise and makes it easier to access basic rights such as health and education. Therefore, the development of a country's infrastructure is directly related to the economic power and quality of life of the people who live there. However, due to the constant increase in the population, the need of developing a greater amount of infrastructure works has never reduced the necessity of making more infrastructure works according to the needs of the country and its citizens. The main objective of this project is to characterize the fourth-generation road concession of the Bucaramanga - Barrancabermeja - Yondó highway (Ruta del Cacao), a Public-Private Partnership project that was tendered in Colombia and whose contract signing date was carried out in the 2015. In order to achieve this objective, in first place it is going to be done a literature review about the chapters 6 and 14 of the book 'Public-private 4 Partnerships by Yescombe (2007), a text that talk about contract management, evaluation and transfer of risks in public works. Afterwards, the bidding processes of the project will be analyzed in order to know the risk management in the particular case of analysis to finally conclude based on the generalities of the literature.